1979
DOI: 10.1073/pnas.76.11.5882
|View full text |Cite
|
Sign up to set email alerts
|

A practicable immunological approach to block spermatogenesis without loss of androgens.

Abstract: The intrinsic capacity of the immune system to elicit immune response selectively against late developing sperm proteins has been mobilized to intercept spermatogenesis. Bacillus Calmette-Guerin given in appropriate doses intratesticularly is effective in bringing about this effect. In dogs and rhesus monkeys, the sperm count in the semen declined precipitously, and almost complete azospermia was attained in 4-6 weeks after immunization. The few sperm cells that were present were immotile. Examination of seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…4p). This mode of immunization does not cause a fall in the blood androgen levels as reported elsewhere (Talwar et al 1979). (2) At high doses (75-1 10 units), Fig.…”
Section: Hiitology Of the Testessupporting
confidence: 80%
See 1 more Smart Citation
“…4p). This mode of immunization does not cause a fall in the blood androgen levels as reported elsewhere (Talwar et al 1979). (2) At high doses (75-1 10 units), Fig.…”
Section: Hiitology Of the Testessupporting
confidence: 80%
“…It further reports the effective use of an attenuated mycobacterium BCG, which has been in clinical use for decades, for immuiiological sterilization of dogs with no serious side effects. The rationale, wide applicability and benefits of BCG as an agent to achieve aspermatogenesis in mammals have been discussed elsewhere (Talwar et al 1979).…”
mentioning
confidence: 99%
“…Immunogens that can be used in males are currently restricted to follicle-stimulating (FSH), luteinizing (LH) and gonadotrophin-releasing (GnRH) hormones, although immunization with nonspecific proteins has also been suggested (Talwar et al, 1979). The choice of oFSH as an immunogen was based on the results of an earlier study in which we showed that chronic passive immunoneutralization of endogenous FSH of adult male monkeys with characterized antiserum to oFSH leads to a drastic reduction in number of spermatozoa and onset of infertility (Murty et ai, 1979a;Sheela Rani et ai, 1978), but the fertility of these monkeys could be restored by stopping antiserum injections.…”
Section: Introductionmentioning
confidence: 99%
“…Leydig cells are however present intact histologically and are functional. Blood testosterone levels are undiminished [34]. Administration of gonadotropins such as hCG evokes a normal response with rise in blood testosterone levels (Fig.…”
Section: An Alternative Approach To Achieve Aspermatogenesismentioning
confidence: 99%
“…A critically important component in the FCA is the mycobacteria 1241. Use was made of an attenuated mycobacterium-Bacillus Calmette Guerin (BCG) [34]. BCG has been of considerable value in immunoprophylaxis against tuberculosis and in immunotherapy of some cancers [16].…”
Section: An Alternative Approach To Achieve Aspermatogenesismentioning
confidence: 99%